2012
DOI: 10.5194/bg-9-4385-2012
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate leaching from short-hydroperiod floodplain soils

Abstract: Abstract.Numerous studies have shown the importance of riparian zones to reduce nitrate (NO − 3 ) contamination coming from adjacent agricultural land. Much less is known about nitrogen (N) transformations and nitrate fluxes in riparian soils with short hydroperiods (1-3 days of inundation) and there is no study that could show whether these soils are a N sink or source.Within a restored section of the Thur River in NE Switzerland, we measured nitrate concentrations in soil solutions as an indicator of the net… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…In previous studies at this field site, it was shown that the riparian zones and water level changes are important constraints on the distribution and availability of OC and NO − 3 resulting in spatially and temporally highly variable biogeochemical activities (Huber et al, 2012;Peter et al, 2012a,b;Shrestha et al, 2014). We hypothesized that the formation of excess air in response to the hydraulic condition of the river additionally constrains these biogeochemical processes.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…In previous studies at this field site, it was shown that the riparian zones and water level changes are important constraints on the distribution and availability of OC and NO − 3 resulting in spatially and temporally highly variable biogeochemical activities (Huber et al, 2012;Peter et al, 2012a,b;Shrestha et al, 2014). We hypothesized that the formation of excess air in response to the hydraulic condition of the river additionally constrains these biogeochemical processes.…”
Section: Introductionmentioning
confidence: 84%
“…In the framework of an interdisciplinary study in a restored riparian section of the River Thur, Switzerland, pronounced hot spots and moments (McClain et al, 2003) for these biogeochemical processes were identified (Peter et al, 2012a,b). Especially flood events locally intensified OC turnover in the groundwater and impacted N transformation pattern in the riparian soils (Huber et al, 2012;Shrestha et al, 2014). Furthermore, during flood events, significant amounts of air can be delivered to groundwater by the entrapment and dissolution of air bubbles in response to water table fluctuations or groundwater recharge (Mächler et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In both systems, we combined geochemical, biochemical and molecular-biological analysis to identify biogeochemical processes as well as the responsible organisms and to determine process rates and element fluxes (Huber et al, 2012b;Peter et al, 2012a;Samaritani et al, 2011;Shrestha et al, 2012Shrestha et al, , 2014. The results are briefly discussed in Sects.…”
Section: Biogeochemistry: Dynamics Of Organic Carbon Nutrients and Pollutants In Groundwater And Floodplain Soilsmentioning
confidence: 99%
“…First, hot spots of N 2 O (a major greenhouse gas) efflux can occur, in particular during the drying phase after major floods . Second, under unsaturated but sufficiently moist conditions, strong nitrification leads to the accumulation of high amounts of nitrate that are leached to the groundwater mainly during floods and in winter (Huber et al, 2012b). Hence, groundwater quality in near-river aquifers of restored river reaches could vary markedly because of the high spatial and temporal variability of both infiltration travel times and soil properties, in particular on gravel bars.…”
Section: What Are Potential Adverse Effects Of River Restoration?mentioning
confidence: 99%
“…In both systems, we combined geochemical, biochemical and molecular-biological analysis to identify biogeochemical processes as well as the responsible organisms and to determine process rates and element fluxes (Huber et al, 2012b;Peter et al, 2012a;Samaritani et al, 2011;Shrestha et al, 2012Shrestha et al, , 2014. The results are briefly discussed in Sects.…”
Section: Biogeochemistry: Dynamics Of Organic Carbon Nutrients and Pmentioning
confidence: 99%